Realistic rendering of the control block generator on the IMPATT diodes - Sili, Ivan; Сілі, Іван Іванович; Сили, Иван Иванович (Dresden: NGO «Europäische Wissenschafts-plattform», 2019)
The paper [1] illustrates a new and an effective energy-information radio-pulse biotechnology for the destruction of potatoes pests such as Colorado beetles
Keywords: frequency; pulse duration; spur impulse; relative frequency instability; maintenance